Development and verification of a prognostic model for colon cancer on pyroptosis-related genes - Wu, Zizhen; Wang, Bo; Ye, Yingjiang; Wang, Shan; Jiang, Kewei (Frontiers in Genetics, 2022)
Background: The role of pyroptosis in cancer has attracted people’s attention in recent years, but its function in colon cancer remains unclear. This study aimed to construct pyroptosis-related model that can effectively predict the prognosis of patients with colon cancer and explore the potential functions of pyroptosis-related genes (PRGs). Methods: We identified 40 differentially expressed PRGs between colon cancer and normal colon tissues. The model was established using the least absolute shrinkage and selection operator (LASSO) Cox regression method, and the patients were divided into high- and low-risk group. Finally, We verified its biological function in vitro based on three PRGs and demonstrated discrepant expression of PRGs within colon cancer and non-tumor tissues at protein level with immunohistochemistry. Results: A pyroptosis-related prognosis model was constructed, which divided 446 patients with colon cancer into high and low-risk group. Kaplan–Meier analysis results showed that the survival of patients with colon cancer in the high-risk group was worse than that in the low-risk group. Finally, we also confirmed that this score is an independent prognostic factor for colon cancer progression. Conclusions: In summary, the model established by three PRGs was a reliable indicator for predicting prognosis, suggesting that pyroptosis might be a noteworthy therapeutic target in CC.